Stolephorus grandis, a new anchovy (Teleostei: Clupeiformes: Engraulidae) from New Guinea and Australia - Hata, Harutaka; Motomura, Hiroyuki (Zootaxa, 2021)
The new anchovy Stolephorus grandis n. sp., described on the basis of 10 specimens collected from Papua, Indonesia, and Australia, closely resembles Stolephorus mercurius Hata, Lavoué & Motomura, 2021, Stolephorus multibranchus Wongratana, 1987, and Stolephorus rex Jordan & Seale, 1926, all having double pigmented lines on the dorsum from the occiput to the dorsal-fin origin, a long maxilla (posterior tip just reaching or slightly beyond the posterior margin of preopercle), and lacking a predorsal scute. However, the new species clearly differs from the others in having fewer gill rakers (35–39 total gill rakers on the first gill arch in S. grandis vs. > 38 in the other species), a greater number of vertebrae (total vertebrae 42–43 vs. fewer than 41), longer caudal peduncle (21.9–23.7% SL vs. < 20.8%), and the depressed pelvic fin not reaching posteriorly to vertical through the dorsal fin-origin (vs. reaching beyond level of dorsal-fin origin).